2022
DOI: 10.1002/jmv.27986
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus persistence during the COVID‐19 pandemic—Impact on pediatric acute wheezing presentations

Abstract: Rhinoviruses have persisted throughout the COVID‐19 pandemic, despite other seasonal respiratory viruses (influenza, parainfluenza, respiratory syncytial virus, adenoviruses, human metapneumovirus) being mostly suppressed by pandemic restrictions, such as masking and other forms of social distancing, especially during the national lockdown periods. Rhinoviruses, as nonenveloped viruses, are known to transmit effectively via the airborne and fomite route, which has allowed infection among children and adults to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 25 publications
4
12
0
Order By: Relevance
“…Thus, the COVID‐19 pandemic and social distancing did not similarly affect all respiratory viruses. The persistence of adenovirus, HMPV, parainfluenza viruses and possibly also rhinovirus, in our study, may explain the observation of the unchanged occurrence of respiratory admissions for asthma, wheezing, and croup, which are known to be associated with these infections 18,35–37 …”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Thus, the COVID‐19 pandemic and social distancing did not similarly affect all respiratory viruses. The persistence of adenovirus, HMPV, parainfluenza viruses and possibly also rhinovirus, in our study, may explain the observation of the unchanged occurrence of respiratory admissions for asthma, wheezing, and croup, which are known to be associated with these infections 18,35–37 …”
Section: Discussionsupporting
confidence: 49%
“…The persistence of adenovirus, HMPV, parainfluenza viruses and possibly also rhinovirus, in our study, may explain the observation of the unchanged occurrence of respiratory admissions for asthma, wheezing, and croup, which are known to be associated with these infections. 18,[35][36][37] Importantly, even though we did not observe a reduction in the overall detection of some respiratory viruses, we did notice a change F I G U R E 3 Respiratory viruses (RSV, influenza viruses, HMPV, adenovirus, and parainfluenza viruses) observed weekly prevalence and forecasted weekly prevalence, during the study period (January 2015-August 2021). Forecasts were computed using unobserved-components time series models (UCM procedure in STATA 15.1).…”
Section: Respiratory Viral Pcr Panel Results and Associated Respirato...mentioning
confidence: 59%
See 1 more Smart Citation
“…Influenza A viruses and RVs allowed the rapid increase of RV infections. 18 In this study, RV was also found to be a substantial…”
Section: Influenza a Virus Infections: The Lack Of Viral Interference...supporting
confidence: 57%
“…The reason was proposed that although surgical face masks can prevent the transmission of seasonal influenza viruses, they may not be effective to prevent the transmission of RVs which is a nonenveloped virus. Further, it has been suggested that the high prevalence of RV infections during the COVID‐19 pandemic was due to the decrease in the prevalence of Influenza A virus infections: the lack of viral interference between I nfluenza A viruses and RVs allowed the rapid increase of RV infections 18 . In this study, RV was also found to be a substantial respiratory pathogen in 2019, 2020, and 2021; however, no significant difference was observed in the infection ratio among the three years.…”
Section: Discussionmentioning
confidence: 99%